The secret at Jefferson's mansion - Roy, Ron; Bush, Timothy (New York : Random House, 2009)
While visiting Thomas Jefferson's home, Monticello, presidential stepdaughter KC Corcoran and her friend Marshall investigate the theft of a box of toy horses given to Jefferson by his grandchildren.
"A Stepping Stone book."
Keywords: Jefferson, Thomas; Mystery and detective stories; Presidents